2015
DOI: 10.1097/bot.0000000000000356
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Syndesmotic Overcompression After Fixation of Ankle Fractures With a Syndesmotic Injury

Abstract: Objectives The goals of this study were to assess syndesmotic reductions utilizing computerized tomography (CT) scans, and to determine if malreductions were associated with certain injury types or reduction forceps. Design Prospective cohort Setting Urban Level 1 Trauma center Patients Twenty-seven patients with operatively treated syndesmotic injuries were recruited prospectively. Intervention Patients underwent postoperative bilateral CT scans of the ankle and hindfoot to assess syndesmotic reductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 43 publications
1
31
0
Order By: Relevance
“…This suggests that there was a net compression effect or medial translation, rather than rotational malreduction. This finding is consistent with studies by Haynes et al [ 28 ] and Cherney et al [ 29 ] that showed overcompression was likely during reduction clamping of the syndesmosis, with a mean of 1 mm of overcompression and 5° of external rotation. Similar results were found in a cadaveric study by Phisitkul et al [ 25 ], which showed a mean syndesmosis displacement of 0.1 ± 0.77 mm in all degrees of instability and overcompression of 0.93 ± 0.70 mm during clamping, with the clamp in the neutral anatomical axis.…”
Section: Discussionsupporting
confidence: 92%
“…This suggests that there was a net compression effect or medial translation, rather than rotational malreduction. This finding is consistent with studies by Haynes et al [ 28 ] and Cherney et al [ 29 ] that showed overcompression was likely during reduction clamping of the syndesmosis, with a mean of 1 mm of overcompression and 5° of external rotation. Similar results were found in a cadaveric study by Phisitkul et al [ 25 ], which showed a mean syndesmosis displacement of 0.1 ± 0.77 mm in all degrees of instability and overcompression of 0.93 ± 0.70 mm during clamping, with the clamp in the neutral anatomical axis.…”
Section: Discussionsupporting
confidence: 92%
“…Multiple biomechanical and clinical studies have demonstrated that medial overcompression of the distal tibiofibular articulation is possible during operative fixation. 3,13,17,21 Cherney et al 3 reported in a prospective study that 44% of patients (12/27) had significant postoperative fibular medialization relative to the contralateral side following syndesmotic reduction and quadcortical screw fixation. Hayes et al 13 investigated the amount of force applied during clamp reduction during syndesmotic repair in a case-control series.…”
Section: Discussionmentioning
confidence: 99%
“…16,19 Recent data from our institution revealed that 12 of 27 patients (44%) treated with syndesmotic reduction and fixation had excessive medialization of the fibula by greater than 1.0 mm when compared with the contralateral uninjured ankle on postoperative CT scan. 5 Overcompression of the syndesmosis may limit physiologic ankle motion, affect functional and subjective outcomes, and possibly contribute to accelerated chondrosis and eventual osteoarthritis.…”
Section: Introductionmentioning
confidence: 99%